Determination of prevalence of paratuberculosis in dairy cattle by polymerase chain reaction (PCR) - Çetinkaya, B; Muz, A; Ertas, HB; Öngör, H; Sezen, IY; Gülcü, HB (Scientific Technical Research Council Turkey, 2000)
The aim of this study was to determine the prevalence of paratuberculosis in dairy cattle in Elazig and the surrounding villages. A polymerase chain reaction (PCR) based on IS900 an insertion sequence specific to Mycobacterium avium subsp. paratuberculosis, was used to detect mycobacterial DNA in milk samples of 500 dairy cows. The detection limit of the PCR was assessed by spiking a known negative milk sample with a dilution series (1x10(9) to 10 bacteria/ml) of reference M. avium subsp. paratuberculosis culture). In the agarose gel examination of the PCR amplified products, approximately 50 bacteria/ml were detected, in the examination of 500 milk samples, 25 (5.0%) were found to be positive by PCR. Pellet suspensions from PCR positive milk samples were inoculated onto Middlebrook 7H11 + OADC medium containing mycobactin (4 ml/litre), and 17 out of 25 (68%) PCR positive samples were determined to be positive by culture. When the prevalence of the disease was estimated with culture results taken into consideration, it was determined to be 3.4% (17/500), but the difference between this and 5% of the PCR was not statistically significant (p>0.05). In conclusion, it was shown that PCR may successfully be used as an alternative to culture in the diagnosis of subclinical paratuberculosis in live animals. In addition, the finding that M. avium subsp. paratuberculosis was being shed in the milk of animals in a significant proportion, suggests Chat paratuberculosis should also be considered seriously in terms of public health, because of the link between M. avium subsp. paratuberculosis and Crohn disease in man, and because the agent may survive pasteurisation.
Süt İneklerinde Paratüberküloz Prevalansinin Polimeraz Zincir Reaksiyonu (PZR) ile Saptanmasi
Keywords: cattle; milk; prevalence; polymerase chain reaction; culture; paratuberculosis